Study of the effect of wind angles on the aerodynamic characteristics of high-speed trains subjected to a translating simulated tornado - Li, Mu; Gan, Jiankun; Zhang, Yuanzhao; Wu, Yecheng; Chai, Bo (Frontiers in Physics, 2024)
This paper studies the effect of the wind angles on the aerodynamic characteristics of a high-speed train under translating simulated tornado. The small six-dimensional force/torque sensor was used to measure the aerodynamic force and moment of a high-speed train model with a reduced scale of 1:150. Based on the aerodynamic shape difference between the high-speed train head and car, highspeed train models are comprised of high-speed train head model and high-speed train car model. The aerodynamic force and moment coefficient time history of the high-speed train models exhibit non-stationary characteristics. The models, consisting of high-speed train heads and cars with differing aerodynamic shapes, displayed non-stationary characteristics in their respective aerodynamic force and moment coefficient time histories. The variation trends of the pitching moment coefficient ensemble time-varying mean of a high-speed train car and head, for wind angles smaller than 60°and 45°, are different from those of other wind angles, respectively. The lift force coefficient ensemble time-varying mean of the high-speed train head does not haveis asymmetryical along the longitudinal axis when the wind angle is smaller than 60°, which is different from the highspeed train car. The maximum values of ensemble time-varying mean of force and moment coefficient of high-speed train are almost equal under different tornado simulator movement direction at each wind angle, which is also applied for minimum value of force and moment coefficient of high-speed train. The ensemble time-varying variance of the force and moment coefficient of the high-speed train model in the region of -200mm~200mm is greater than that in other region. This study will enhance themay contribute to a more comprehensive and precise understanding of the interaction between tornado and high-speed train.